In Search of Labor Demand - Beaudry, Paul; Green, David A.; Sand, Ben M. (American Economic Review, 2018)
We propose and estimate a novel specification of the labor demand curve incorporating search frictions and the role of entrepreneurs in new firm creation. Using city-industry variation over four decades, we estimate the employment -wage elasticity to be -1 at the industry-city level and -0.3 at the city level. We show that the difference between these estimates likely reflects the congestion externalities predicted by the search literature. Also, holding wages constant, an increase in the local population is associated with a proportional increase in employment. These results provide indirect information about the elasticity of job creation to changes in profits.